ON THE REMINDER OF A TAYLOR–MACLAURIN TYPE GENERAL FORMULA - Sahakyan, B.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
We continue the study started in [1] regarding the Taylor–Maclaurin representation of functions. In the present paper we obtain a more convenient representation for the function Rn(x), the residual term of the generalized Taylor–Maclaurin formula.
Keywords: Weil operators; Taylor–Maclaurin type formulae